Ambient Fast Synthesis and Active Sites Deciphering of Hierarchical Foam‐Like Trimetal–Organic Framework Nanostructures as a Platform for Highly Efficient Oxygen Evolution Electrocatalysis. Issue 23 (11th April 2019) - Qian, Qizhu; Li, Yapeng; Liu, Yi; Yu, Lai; Zhang, Genqiang
Abstract: Metal–organic frameworks (MOFs) have attracted tremendous interest due to their promising applications including electrocatalysis originating from their unique structural features. However, it remains a challenge to directly use MOFs for oxygen electrocatalysis because it is quite difficult to manipulate their dimension, composition, and morphology of the MOFs with abundant active sites. Here, a facile ambient temperature synthesis of unique NiCoFe‐based trimetallic MOF nanostructures with foam‐like architecture is reported, which exhibit extraordinary oxygen evolution reaction (OER) activity as directly used catalyst in alkaline condition. Specifically, the (Ni2 Co1 )0.925 Fe0.075 ‐MOF‐NF delivers a minimum overpotential of 257 mV to reach the current density of 10 mA cm −2 with a small Tafel slope of 41.3 mV dec −1 and exhibits high durability after long‐term testing. More importantly, the deciphering of the possible origination of the high activity is performed through the characterization of the intermediates during the OER process, where the electrochemically transformed metal hydroxides and oxyhydroxides are confirmed as the active species. Abstract : Hierarchical trimetallic NiCoFe‐based metal–organic framework (MOF) nanofoam with modulated molar ratios is successfully synthesized through a developed mild, onepot, ambient‐temperature, solution‐phase method. The nanofoam can be directly utilized as an efficient oxygen evolution reaction (OER) catalyst with extraordinary activity and excellent durability. The metal hydroxide and oxyhydroxide evolved from the pristine MOF structure are demonstrated as the active species for high OER activity.